We need to satisfy the following equations:
x*y = 13
x + y = -14
Isolating x from the first equation,
x = -14 - y
Substituting this result into the first equation,
(-14 - y)*y = 13
-14y- y*y = 13
-y² - 14y - 13 = 0
Using the quadratic formula,
![\begin{gathered} y_(1,2)=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ y_(1,2)=\frac{14\pm\sqrt[]{(-14)^2-4\cdot(-1)\cdot(-13)}}{2\cdot(-1)} \\ y_(1,2)=\frac{14\pm\sqrt[]{144}}{-2} \\ y_1=(14+12)/(-2)=-13 \\ y_2=(14-12)/(-2)=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2wdcv06xu70klo52z2xyyk936071k0352m.png)
Therefore, the solution is: